Analisis Pengelolaan Konten Aplikasi Islam Sebagai Media Informasi - Dede Mercy Rolando (Sekolah Tinggi Agama Islam Publisistik Thawalib Jakarta, 2022)
This study aims to see how the management of content in the Islamic Question and Answer application as a medium of Islamic information. This research is included in the qualitative category, with a content analysis approach and in its presentation using a descriptive method. The object of research in this case is the Islamic Question and Answer Application. The data collection technique that the author uses is through 3 interview techniques, observation and documentation. The data analysis technique that the author uses is semiotic analysis. The results of the analysis of the content management analysis of the Islamic Q&A application are through several processes, including first, user questions. Second, it is efficacious to answer. Third, re-checking the cyber team and the documentation team. Fourth, content presentation. In addition, the existence of the Islamic Question and Answer application is a combination of various forms of religious convergence and provides religious information. Where this application makes it easier for Muslims in the media era as it is now and presents the presence of Muslims as part of a media-literate and techno-literate society.